2020
DOI: 10.3390/catal10040439
|View full text |Cite
|
Sign up to set email alerts
|

Semiconductor Electrode Materials Applied in Photoelectrocatalytic Wastewater Treatment—an Overview

Abstract: Industrial sources of environmental pollution generate huge amounts of industrial wastewater containing various recalcitrant organic and inorganic pollutants that are hazardous to the environment. On the other hand, industrial wastewater can be regarded as a prospective source of fresh water, energy, and valuable raw materials. Conventional sewage treatment systems are often not efficient enough for the complete degradation of pollutants and they are characterized by high energy consumption. Moreover, the chem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
52
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(54 citation statements)
references
References 220 publications
(240 reference statements)
0
52
1
1
Order By: Relevance
“…The photodegradation of various organic compounds by different semiconductor materials has been previously studied. 2,4,30 It was demonstrated that electrochemical assistance (i.e., working potentials ranged from 0.2 to 0.8 V versus Ag−AgCl) enhances the efficiency of the latter process, leading to quite efficient CO 2 conversion. 4,30−34…”
Section: Resultsmentioning
confidence: 99%
“…The photodegradation of various organic compounds by different semiconductor materials has been previously studied. 2,4,30 It was demonstrated that electrochemical assistance (i.e., working potentials ranged from 0.2 to 0.8 V versus Ag−AgCl) enhances the efficiency of the latter process, leading to quite efficient CO 2 conversion. 4,30−34…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the electrochemical performance at different external resistance values was also evaluated. As shown in Figure 4b, the output potential and current density all decreased with the increases in external resistance owing to the large diffusional resistance and overpotential [39,40]. Hence, the current density decreased from 0.41 to 0.07 A m −2 when the external resistance increased from 500 to 5000 Ω.…”
Section: Effect Of External Resistancementioning
confidence: 92%
“…According to the previous works, [53][54][55] there are many radicals generated during the photodegradation process, as represented in the following equations (3-9) (Scheme 1):…”
Section: Photocatalytic Activitymentioning
confidence: 99%